2013
DOI: 10.3813/aaa.918609
|View full text |Cite
|
Sign up to set email alerts
|

Loudness of Speech and Speech-Like Signals

Abstract: The influence of different properties of speech-likesignals on loudness wasinvestigated by measuring levels at equal loudness in normal-hearing listeners for 22 speech-likes timuli using categorical loudness scaling and an adaptive matching procedure. Eight of the stimuli, referred to as unprocessed stimuli, had the same speech-like long-term spectrum, butdiffered in other speech-related properties, ranging from astationary noise overspeechmodulated signals to real intelligible and unintelligible speech. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The results of the experiments are consistent with earlier results showing that the LTL predicted by the TVL model could give accurate predictions of the loudness of speech that had been subjected to multi-channel amplitude compression of the type that is often used in broadcasting (Moore et al, 2003). It is also consistent with the results of Rennies et al (2013), obtained using both loudness matching and categorical loudness scaling, which showed that the LTL gave reasonably accurate predictions of the loudness of a variety of speech-like signals (including speech-shaped noise, unprocessed speech, and speech that was subjected to filtering, reverberation, and amplitude compression and expansion), whereas the predictions were not as accurate when based on the short-term loudness derived using the TVL model or other loudness models (Chalupper and Fastl, 2002;Rennies et al, 2009). Table II summarizes the results of the two experiments, showing the mean adjustments in level relative to equal RMS required to equalize the peak LTL or the mean LTL and the mean rating obtained for each equalization method and type of processing.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the experiments are consistent with earlier results showing that the LTL predicted by the TVL model could give accurate predictions of the loudness of speech that had been subjected to multi-channel amplitude compression of the type that is often used in broadcasting (Moore et al, 2003). It is also consistent with the results of Rennies et al (2013), obtained using both loudness matching and categorical loudness scaling, which showed that the LTL gave reasonably accurate predictions of the loudness of a variety of speech-like signals (including speech-shaped noise, unprocessed speech, and speech that was subjected to filtering, reverberation, and amplitude compression and expansion), whereas the predictions were not as accurate when based on the short-term loudness derived using the TVL model or other loudness models (Chalupper and Fastl, 2002;Rennies et al, 2009). Table II summarizes the results of the two experiments, showing the mean adjustments in level relative to equal RMS required to equalize the peak LTL or the mean LTL and the mean rating obtained for each equalization method and type of processing.…”
Section: Discussionsupporting
confidence: 93%
“…The level of the reference signal was fixed at 70 dB SPL. The level of the test signal was set adaptively depending on the subject's response (for details, see Rennies et al, 2013). This procedure resulted in an estimate of the level at which the test signal was perceived as equally loud as the reference signal (presented at the reference level).…”
Section: Loudness Matchingmentioning
confidence: 99%
“…For each measurement, this procedure resulted in a categorical loudness function of cu values vs. sound pressure level. These functions were then used to derive level differences at equal loudness by computing the horizontal distance between the loudness function of the reference signal and all other loudness functions at the cu value corresponding to a level of 70 dB SPL for the reference signal (i.e., the reference level; for details, see Rennies et al, 2013). The same apparatus as for the loudness scaling experiments was used.…”
Section: Categorical Loudness Scalingmentioning
confidence: 99%
See 2 more Smart Citations